Chinese gay men's coming out narratives: Connecting social relationship to co-cultural theory. Issue 4 (1st October 2016) - Bie, Bijie; Tang, Lu
ABSTRACT: Theorizing the intersection of queer identity and culture values, this study examines Chinese gay men's coming-out experiences through a narrative analysis of 60 self-reported stories online. It finds that Chinese gay men's decision to come out, their communication orientations, and the outcomes of their coming out are influenced by traditional Chinese cultural values such as family, marriage, and duty. Assertive assimilation, assertive accommodation, and nonassertive accommodation are the most used communication orientations. The study adds to co-cultural theory by demonstrating that types of social relationships affect the communication orientations adopted, at least in the context of China.